KOMPONEN SINDROMA METABOLIK SEBAGAI FAKTOR RISIKO TERHADAP GEJALA DEPRESI - , PRAHASTYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The prevalence of metabolic syndrome is high enough around the world, its prevalence appears to be increasing due to the enhancement of obesity prevalence in parallel. According to the World Health Association (WHO), the metabolic syndrome is a new pandemic of the 21st century. It is estimated that number of metabolic syndrome patients increased more than 50% at 20 years. Some studies showed that the incidence of depression will increase in patients with hypertension, diabetes mellitus type 2 and poor glycemic control in patients with diabetes mellitus type 2 with depression, dyslipidemia, and central obesity. Objective: To determine the role of metabolic syndrome components as a risk factor for depressive symptoms. Methods : The study conducts with a case-control study design. All the samples are taken from patients treated at the Endocrinology Clinic of Dr. Sardjito hospital Result : The subjects comprised of 18 patients in the case group and 18 patients in the control group consist of 10 (55.6%) female subjects and 8 (8.44%) male subjects in each group. Baseline characteristics shows there was no significant differences in mean age, BMI, systolic blood pressure, diastolic blood pressure, LDL cholesterol and total cholesterol in both groups. There were significant differences in the mean waist circumference, fasting blood glucose, triglycerides and HDL cholesterol in both groups, whereas in the case group had a higher score than the control group, except for HDL cholesterol. On bivariate analysis, a significant association high triglyceride level (OR = 5.2